Three little words - Holiday, Jenny (Romance author) (Holiday, Jenny (Romance author) Bridesmaids behaving badly., 2019)
After getting stranded with her best friend's wedding dress, Gia Gallo shares a car with best man Bennet Buchanan for a long road trip to the wedding in Florida, during which they have difficulty resisting their mutual passion.